EVALUATION OF CONTRACT CHEATING PREVENTION THROUGH FINAL PROJECT CHOICE POLICY - Ansyari, Rizli; Wibowo, Udik Budi (Universitas Labuhanbatu, 2024)
Contract cheating is a serious problem faced by universities today that must be prevented immediately. This academic crime is mostly committed during the final project by students so so that each campus must have a clear policy to overcome this problem. After implementing the policy, it is necessary to conduct an evaluation to see whether the policy needs to be continued or not. The research design used is mixed methods, with a goal-oriented evaluation model. Quantitative data collection techniques were carried out by conducting surveys to alumni and qualitative data collection techniques used were interviews and documentation studies. The evaluation results show that this policy has a positive impact in reducing and preventing the practice of contract cheating in students' final projects. This result is also supported by campus assertiveness towards staff involved in this fraudulent practice.